Clinical Correlates of Benefit From Radium‐223 Therapy in Metastatic Castration Resistant Prostate Cancer. Issue 5 (19th December 2016) - Alva, Ajjai; Nordquist, Luke; Daignault, Stephanie; George, Saby; Ramos, Jorge; Albany, Costantine; Isharwal, Sudhir; McDonald, Matthew; Campbell, Gregory; Danchaivijitr, Pongwut; Yentz, Sarah; Anand, Aseem; et al.
Abstract : BACKGROUND: We sought to identify potential clinical variables associated with outcomes after radium‐223 therapy in routine practice. METHODS: Consecutive non‐trial mCRPC patients who received ≥1 dose of radium dichloride‐223 at four academic and one community urology‐specific cancer centers from May 2013 to June 2014 were retrospectively identified. Association of baseline and on‐therapy clinical variables with number of radium doses received and clinical outcomes including overall survival were analyzed using chi‐square statistics, cox proportional hazards, and Kaplan–Meier methods. Bone Scan Index (BSI) was derived from available bone scans using EXINI software. RESULTS: One hundred and forty‐five patients were included. Radium‐223 was administered for six cycles in 74 patients (51%). One‐year survival in this heavily pre‐treated population was 64% (95%CI: 54–73%). In univariate and multivariate analysis, survival was highly associated with receiving all six doses of Radium‐223. Receipt of six doses was associated with ECOG PS of 0–1, lower baseline PSA & pain level, no prior abiraterone/enzalutamide, <5 BSI value, and normal alkaline phosphatase. In patients who reported baseline pain (n = 72), pain declined in 51% after one dose and increased in 7%. PSA declined ≥50% in 16% (18/110). Alkaline phosphatase declined ≥25% in 48% (33/69) and ≥50% in 16/69 patients. BSI declined in 17 (68%) of the 25 patients who had bone scan available at treatment follow‐up. Grade ≥3 neutropenia, anemia, and thrombocytopenia occurred in 4% (n = 114), 4% (n = 125), and 5% (n = 123), respectively. CONCLUSIONS: Patients earlier in their disease course with <5 BSI, low pain score, and good ECOG performance status are optimal candidates for radium‐223. Radium‐223 therapy is well tolerated with most patients reporting declines in pain scores and BSI. Prostate 77:479–488, 2017 . © 2016 Wiley Periodicals, Inc.